Fungsi Pemerintah Desa Dalam Pemenuhan Air Bersih Di Desa Bolua Kecamatan Raijua Kabupaten Sabu Raijua - Djami Pau, Rahel; Nuban, Detji K E R; Asnawi, Norani (Artemis Law Journal, 2025)
Based on Article 67 paragraph (2) letter b of Law Number 3 of 2024 concerning the second amendment to Law Number 6 of 2014 concerning Villages, it is stated that the Village is obliged to "improve the mutual life of the local Village community". One of them is by providing clean water needs to improve the welfare of the community in the Village. The need for clean water is currently a major problem for the community in Bolua Village, Raijua District, Sabu Raijua Regency. In Bolua Village, the community has difficulty in obtaining clean water that is healthy and of good quality considering the location of the population which is far from water sources and the area is hilly and sloping and there is no adequate clean water supply system in Bolua Village so that the community needs a lot of time and energy to meet the need for clean water. This study uses empirical legal research. The Implementation of the Function of the Village Government in Fulfilling Clean Water in Bolua Village has not gone well where until now the village community is still having difficulty supplying clean water. The factors that hinder the implementation of the village government's function in providing clean water in Bolua Village are first, internal factors, namely the low quality of human resources, limited budget. Second, external factors, namely limited air resources, natural conditions of the village, and lack of awareness among village communities in maintaining and caring for water sources in the village.